STUDENT EXPERIENCE IN CREATING SIMULATION VIDEOS OF EXPERT WITNESS TESTIMONY IN COURT: FROM THE THEORY TO PRACTICE - Suryadi, Taufik; Mulya, Intan Chaharunia; Kulsum, Kulsum (Universitas Gadjah Mada, 2023)
Background: This study aims to explore the experience of clinical students studying at the Department of Forensic medicine in creating simulation videos of expert witness testimony in court.Methods: This one-center study used a qualitative story telling design. Twenty clinical students volunteered to simulate expert witness testimony in court by taking 59 recorded scenes as teaching materials for preclinical medical students. The room was set resembling to a courtroom following the instruction of scriptwriter and director by lecturer. Students were distributed into several playing characters such as judges, prosecutors, lawyers, defendant and doctors, while others served as assistant directors, cameramen, narrator, scene takers, artistic directors, equipment stylists, and editors. The scenario is outlined in detailed scenes to guide the students in performing the characters. After completing the simulation, each student reflected on their experience during the creation of simulation video. The results of these reflections are then compiled into a learning concept adjusting to narrative medicine.Result: Students claimed that they obtained new experiences during the learning process. The experience allowed students to learn in more interesting way by transforming theory into practice. Students also agreed on proposing this learning channel as a breakthrough in learning process. Creating simulation video plays a significant role in the audiovisual learning process which supported students comprehending the process of giving an expert witness testimony.Conclusion: Transforming education into video simulation is recommended as a game changer in a learning process. Most medical students are likely to absorb the knowledge better when it is applied into video simulation.